Estudo do potencial antitumoral do óleo essencial das folhas de Lippia microphylla Cham. (Verbenaceae) e sua toxicidade - Xavier, Aline Lira (2011)
Cancer is a complex genetic disease that is a major public health problem worldwide accounting for about seven million of deaths each year. Many anticancer drugs currently used in clinical medicine have been isolated from plant species, or they are based on substances isolates of these species. But natural products, as anticancer agents, can also cause damage to the organism, requiring toxicity studies. Lippia microphylla is a plant popularly known as alecrim-de-tabuleiro, rarely reported in literature. There are several reports of constituents isolated from species of this genus that have antitumor activity, which sparked interest in the investigation of a possible antitumor activity of Lippia microphylla. Additionally, essential oils isolated from different species are known to have different biological activities, among them anticancer activity. Therefore this study aimed to evaluate the antitumor activity and toxicity of essential oil of this species through in vitro and in vivo. Initially was evaluated the in vitro antitumor activity against cell lines sarcoma 180 and K562. The IC50 values obtained were 100, 1 μg/mL and 60.05 μg/mL for the two strains respectively. Investigation of the mechanism of cytotoxicity (intrinsic pathway of apoptosis and involvement of oxidative stress) through supplementation of culture medium with cyclosporin A and the antioxidants glutathione and N-acetylcysteine resulted in IC50 of 118,3 μg/mL, 107,3 μg/mL e 109,2 μg/mL for sarcoma 180 respectively, and 51.94 μg/mL, 55.49 μg/mL and 94.18 μg/ml for K562, respectively. The CH50 value obtained in the experiment of cytotoxicity against erythrocytes was 300.2 μg/mL. In the evaluation of antitumor activity the in vivo inhibition rates of tumor growth were 38.2% for the dose of 50 mg/kg and 59.8% for 100 mg/kg of essential oil of Lippia microphylla (OEL). The toxicological analysis showed moderate gastrointestinal and hematological toxicity, and alterations in liver function, as evidenced by an increase in AST and ALT, corroborated with histopathological analysis, for both groups treated with OEL. However the changes are reversible and not considered substantial when compared with several widely anticancer drugs used in clinical medicine. Therefore, we can infer that the O.E.L. displays antitumor activity in vitro and in vivo with moderate toxicity, which is not a limiting factor for its possible pharmacology applicability.